2005
DOI: 10.1152/ajpheart.00317.2005
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) binds to specific receptors on cardiac fibroblasts to initiate antifibrotic and antitrophic effects

Abstract: ANG-(1-7) improves the function of the remodeling heart. Although this peptide is generated directly within the myocardium, the effects of ANG-(1-7) on cardiac fibroblasts that play a critical role in cardiac remodeling are largely unknown. We tested the hypothesis that specific binding of ANG-(1-7) to cardiac fibroblasts regulates cellular functions that are involved in cardiac remodeling. 125I-labeled ANG-(1-7) binding assays identified specific binding sites of ANG-(1-7) on adult rat cardiac fibroblasts (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
183
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(205 citation statements)
references
References 30 publications
16
183
1
5
Order By: Relevance
“…The fact that collagen VI undergoes an opposite change as that observed for collagen I, III, and fibronectin suggests that this influence is selective. These observations are in accordance with a recent report by Iwata et al, 17 showing that Ang-(1-7) produces antifibrotic effects. As expected, 24,27 a contribution of BP to the changes in collagen expression or in cardiac function could be excluded by the direct BP measurements in halothane-anesthetized and in nonanesthetized mice.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The fact that collagen VI undergoes an opposite change as that observed for collagen I, III, and fibronectin suggests that this influence is selective. These observations are in accordance with a recent report by Iwata et al, 17 showing that Ang-(1-7) produces antifibrotic effects. As expected, 24,27 a contribution of BP to the changes in collagen expression or in cardiac function could be excluded by the direct BP measurements in halothane-anesthetized and in nonanesthetized mice.…”
Section: Discussionsupporting
confidence: 94%
“…36 More recently, it has been demonstrated in humans that treatment with aldosterone antagonists substantially increased ACE2 activity. 38 The prominent decrease in cardiac function in Mas Ϫ/Ϫ mice, which can be correlated with the marked changes in extracellular matrix proteins and the antihypertrophic effects of Ang-(1-7), 16,17 apparently mediated by its interaction with Mas, 18 suggest that activation of the Ang-(1-7)-forming pathways by RAS blockade produces beneficial cardiac effects through activation of Mas. One could argue that ACE2 knockout mice 39 showed more pronounced cardiac function impairment than Mas knockout mice.…”
Section: Perspectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, chronic Ang-(1-7) treatment not only attenuated the development of heart failure in response to coronary artery ligation in rats (Loot et al 2002), but it also reversed cardiac hypertrophy and fibrosis in rats (Iwata et al 2005;Tallant et al 2005;Wang et al 2005;Grobe et al 2006a;2006b). Ishiyama et al (2004) found that heart failure induced by coronary artery ligation was associated with an increase in plasma Ang-(1-7) levels, which was augmented with the administration of the AT 1 receptor blockers losartan and olmesartan.…”
Section: Aj Trask and CM Ferrariomentioning
confidence: 99%
“…1). These include antihypertensive, antiarrhythmic, cardioprotective anti-inflammatory, anti-fibrotic, anti-thrombotic and antitrophic effects in a number of different cell types (Benter et al 1995;Ferreira et al 2001Ferreira et al , 2002Freeman et al 1996;Grobe et al 2006;Iwata et al 2005;Kucharewicz et al 2000Kucharewicz et al , 2002Strawn et al 1999;Tallant et al 2005). Ang-(1-7) is degraded by ACE into the inactive peptide Ang-(1-5).…”
Section: Introductionmentioning
confidence: 99%